Green technology system for UiTM Pahang farm application / Syamsyir Akmal Senawi ...[et al.] - Senawi, Syamsyir Akmal; Wan Razali, Wan Aizuddin; Mohd Noor, Badrul Hisham; Sulaiman, Nasharudin (2009)
Green technology or clean technology is the application of the environmental science to conserve the natural environment and resources and reduce the negative impacts of human activities to their surroundings. Hence, this study was carried out to investigate the feasibility and costs involved in applying green technologies for UiTM Pahang farm applications. In the study, only the application of a photovoltaic system was investigated. The total cost to build the full system of green technology was estimated for two potential areas; to support the requirement of maintaining 40 head goats and a sprinkler system for a 0.5-hectare vegetable garden. Based on the assessment conducted, the cost of energy for both systems based on duration of 20 years is RM 0.05/kWh and RM 2.84/kWh respectively. On the other hand, the capital cost to build the systems is calculated to be at RM 9,004.65 and RM 191,835.06 respectively. The results show that maintaining a vegetable garden is more energy intensive between the two activities, and high capital cost involved might be prohibitive. However, using a photovoltaic system to maintain goats is found to have a good potential.